Economic, Environment, and Social Welfare in the Mineral Economy Provinces of Eastern Indonesia - Ramadanti, Sarindang Suci; Azwardi; Subardin, Muhammad (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2024)
This study explores the relationships between economic growth, environmental quality, and social welfare in the mineral economy provinces of Eastern Indonesia, which are heavily dependent on the mining sector—using simultaneous equation models and secondary data from 2015–2022. Empirical results show a bidirectional causal relationship between EQI and HDI, suggesting that improvements in environmental quality enhance human development, and higher human development levels contribute to better environmental quality. Additionally, a unidirectional causal relationship between EQI and GDP indicates that improvements in environmental quality can lead to economic growth. Still, economic growth alone does not necessarily lead to improvements in environmental quality.